Pengaruh Cita Rasa, Harga, dan Kualitas Layanan terhadap Kepuasan Konsumen Lekasane Street Coffee Yogyakarta - Saputro, Pramuditha Nanda; Risdwiyanto, Andriya; Nuralam, Nuralam (Universitas Proklamasi 45, 2025)
The research that will be carried out begins with the large number of street coffees in Yogyakarta, where competition between street coffees is increasing because at affordable prices consumers can enjoy coffee with interesting flavors. This research aims to analyze the influence of taste, price and service quality on consumer satisfaction at Lekasane Street Coffee Yogyakarta. The population in this research is an unknown number of customers of Street Coffee Lekasane Yogyakarta and the sampling technique used is a non-probability sampling technique with purposive sampling which resulted in a total of 73 respondents and the analytical tool used in this research is multiple linear regression. The method used in collecting data is using questionnaires that are distributed to consumers.Based on the results of data analysis, it can be concluded that taste, price and service quality simultaneously have a significant positive impact on consumer satisfaction from Lekasane Street Coffee. Each variable has a very significant influence on consumer satisfaction.